2020
DOI: 10.1071/cp19308
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen supply in combination of nitrate and ammonium enhances harnessing of elevated atmospheric CO2 through improved nitrogen and carbon metabolism in wheat (Triticum aestivum)

Abstract: Elevated carbon dioxide (e-CO2) levels from ambient (a-CO2) enhance plant biomass production and yield. However, this response is highly dependent on the availability and possibly the form of nitrogen (N) supply to plants. This study aimed to investigate changes in C and N metabolism of wheat (Triticum aestivum L.) in response to e-CO2 and N source. e-CO2 enhanced net CO2 assimilation but at highly variable rates depending on the form of N supply. Under e-CO2, net CO2 assimilation rate was in the order NO3– &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…However, little has been done in terms of using 15 N tracing under field conditions to study the effect of N fertilizers on N accumulation and partitioning in spring wheat in the study area. Fewer research efforts have been conducted on how N fertilization affects plant 15 N (Wang et al, 2016), with previous studies yielding contradicting results (Khalil et al, 2020;Agisho and Hairat, 2021) along with the comparison of N sources being emphasized more frequently (Asif et al, 2020). We hypothesized that the longterm application of inorganic nitrogen fertilizers would impact the relationship between N supply and crop N uptake, and thereby N use efficiency and grain yield.…”
Section: Introductionmentioning
confidence: 88%
“…However, little has been done in terms of using 15 N tracing under field conditions to study the effect of N fertilizers on N accumulation and partitioning in spring wheat in the study area. Fewer research efforts have been conducted on how N fertilization affects plant 15 N (Wang et al, 2016), with previous studies yielding contradicting results (Khalil et al, 2020;Agisho and Hairat, 2021) along with the comparison of N sources being emphasized more frequently (Asif et al, 2020). We hypothesized that the longterm application of inorganic nitrogen fertilizers would impact the relationship between N supply and crop N uptake, and thereby N use efficiency and grain yield.…”
Section: Introductionmentioning
confidence: 88%
“…Nitrogen is a fundamental element of life and a major constituent of nucleic acids, amino acids, proteins, chlorophyll and other biomolecules (Asif et al 2020). Studies have found nitrogen addition increases plant foliar nitrogen content (Li et al 2021), thus appropriate nitrogen fertilization promotes plant nitrogen uptake and accumulation.…”
Section: Effects Of Different Nitrogen Forms On Plant and Soil Charac...mentioning
confidence: 99%